On the electromagnetic symmetry producing fields charges at four bosons association - Doria, R.; Mendes, L.S. (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Physics would like to know what electric charge is. As a matter property it generates EM fields, coupling constant, conserved current. Nevertheless Maxwell is uncomplete. It requires to be extended. An approach is supported by electric charge transfer phenomenology. Consider on three flavours charges +, 0, − transmission. A generic electric charge is defined by the triad +, 0, −. It provides an exchange charge physics through the quadruplet Aμ, Uμ, V ± μ . An electromagnetic symmetry is constituted. It associates the four vectorial bosons. The EM completeness of particles carrying three electric charges is found. A four photons EM is derived. It includes, Aμ as the usual photon, Uμ massive photon, V ± μ massive charged photons. A new electromagnetic physics is expressed through an enlarged abelian symmetry, Uq(1). Maxwell relationships between charge and fields are extended. Fields charges are more primitive than electric charge. Noether theorem improves the attributes on electric charge conservation, symmetry equation and constraint. The symmetry equation which govern the electric charge dynamics shows a charge behaviour beyond matter, as fields flux. EM interaction is extended from fine structure constant to modulated and neutral charges. The four bosons electromagnetism introduces a non-univoque electromagnetic symmetry. A pluriformity of EM models is performed under similar abelian group, Uq(1). Opportunities for different EM models are constituted preserving charge conservation law and sharing a common Lagrangian. Physical varieties on Noether theorem, fields strengths, Lagrangian coefficients, equations of motion, fields charges are expressed. Electric charge is englobed by fields charges. The simplest four bosons model is selected. That one which fields strengths are gauge invariants. Propitiating measurable granular and collective fields strenghts. Four kinds of charges are expressed through equations of motion. Electric, modulate, neutral and Bianchi. Allowing to include new EM sectors. Extend Maxwell for nonintegers charges, nonlinearity, neutral EM, spintronics, weak interactions, photonics. A new EM energy emerges.